The role of decentralised managers in decision-making in a large industrial company - Maria C. Tavares; José Vale; Andreia Costa (Administrative Sciences, 2024)
The importance of decentralised managers in the organisational decision-making process has been the subject of studies advocating different concepts. This study aims to comprehend the role of decentralised managers in the decision-making process of a large industrial company. To this end, the case study method was adopted. Semi-structured interviews were conducted with the organisation's top manager and decentralised managers. Based on the results of this investigation, it was possible to see that the organisation's decentralised managers have a high degree of influence on the decision-making process and are responsible for adapting strategies and decisions according to the specific needs of their areas of activity. Therefore, this study significantly contributes to the theoretical and practical understanding of organisational decision-making processes. Furthermore, it provides a valuable foundation for further research into the decision-making processes of decentralised managers, thereby addressing a gap in the existing literature on their influence on organisational decision-making.
Keywords: 350; case study; decentralisation; decentralized management; decision-making; middle managers; Stoner and Freeman